2012
DOI: 10.6017/ital.v31i3.1880
|View full text |Cite
|
Sign up to set email alerts
|

Improving Independent Student Navigation of Complex Educational Web Sites: An Analysis of Two Navigation Design Changes in LibGuides

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 10 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…While some studies found that the tabbed layout rendered the navigation invisible to users, 27 others found that users recognized and liked the tabbed navigation. 28 What is clear in the literature, however, is that design changes to this default navigation such as reducing the number of tabs 29 or changing their visual design 30 can increase usage of the navigation menu (and thus of the guide's subpages). LibGuides 2 makes it possible not just to tweak the design of the menu, but to change its placement.…”
mentioning
confidence: 99%
“…While some studies found that the tabbed layout rendered the navigation invisible to users, 27 others found that users recognized and liked the tabbed navigation. 28 What is clear in the literature, however, is that design changes to this default navigation such as reducing the number of tabs 29 or changing their visual design 30 can increase usage of the navigation menu (and thus of the guide's subpages). LibGuides 2 makes it possible not just to tweak the design of the menu, but to change its placement.…”
mentioning
confidence: 99%
“…Based on the results of the usability testing, HSL modified its citation management tools guide to add a left-hand menu bar containing links to all of the guide's pages to the guide home page. This was found to be an effective improvement to navigation by Eastern Michigan University [13]. As these Guides are used system wide, this finding has implications for the wider library system.…”
Section: Research Guidesmentioning
confidence: 75%
“…Guide design and best practices (for example, number of tabs, tab wording, white space, uniform fonts and colors) make up a large part of the literature (Gonzalez and Westbrock 2010;Hintz et al 2010;Little 2010;Mattson 2013;Pittsley and Memmott 2012;Sonsteby and DeJonghe 2013). Usability -how easily students are able to navigate online guides -is another large area of study.…”
Section: Literature Reviewmentioning
confidence: 99%